Exploration of Physics Problem-Solving Ability in Physics Education College Student: The Concept of Buoyancy - Erniwati Erniwati; Luh Sukariasih; La Tahang; Muh Yuris; Suritno Fayanto (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2022)
This study explored the ability of college students to solve problems involving buoyant force materials. The method used was descriptive qualitative, with the research subjects of Physics Education college students at Halu Oleo University who have programmed the Basic Physics I course. The instrument used was a description of five questions and interview guidelines to explore quantitative findings. The results of the analysis showed that the overall problem-solving ability of college students was still relatively low, with an average score of 40.6. The low problem-solving ability of college students on the concept of buoyancy in expressing the ratio of the lifting force of objects in different fluids determined the lifting force of an object by applying an equation and selecting the buoyancy experienced by an object in a liquid. The difficulties experienced by a college student generally in understanding problems had an impact on completion due to a lack of mastery of concepts. Thus, they could impact appropriately.